2007
DOI: 10.1073/pnas.0704313104
|View full text |Cite
|
Sign up to set email alerts
|

Changes in viral protein function that accompany retroviral endogenization

Abstract: Endogenous retroviruses (ERVs) are the remnants of ancient retroviral infections of germ cells and have been maintained in whole or part as heritable genomic elements. The last known endogenization events occurred several million years ago, and therefore stepwise analysis of retroviral endogenization has not been possible. A unique opportunity to study this process became available when a full-length ERV isolated from koalas (KoRV) was shown to have integrated into their germ line within the past 100 years. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 17 publications
2
74
2
Order By: Relevance
“…CETTG is a motif present in all exogenous and inducible endogenous gammaretroviruses but absent in ERVs. Attenuating this motif by introducing CETAG or CGTAG (in KoRVA isolates) in place of CETTG causes a reduction in cytopathic affects induced by fusion from without (8).…”
Section: Resultsmentioning
confidence: 99%
“…CETTG is a motif present in all exogenous and inducible endogenous gammaretroviruses but absent in ERVs. Attenuating this motif by introducing CETAG or CGTAG (in KoRVA isolates) in place of CETTG causes a reduction in cytopathic affects induced by fusion from without (8).…”
Section: Resultsmentioning
confidence: 99%
“…However, the homology in the 5= UTR of pKoRV522 was relatively low (97.4%), and pKoRV522 contained 6-bp and 3-bp insertions at positions 149 and 387 of pcindy, respectively. In a previous study (6), although both KoRV and GALV utilize the human Pit-1 molecule (a phosphate transporter) to infect human cells, pseudotyped KoRV Env infection was shown to be 1,000 times lower than that of GALV Env pseudotype on MDTF expressing human Pit-1. Further investigation led to the identification of several amino acids involved in the attenuation of Env functions, such as infectivity and fusion activity, of KoRV by comparing KoRV and GALV Env sequences (6).…”
Section: Cellmentioning
confidence: 99%
“…In one study, individual genes derived from a molecular clone of KoRV, termed pcindy, were investigated for their impacts on KoRV-pseudotyped virus infection (6). The authors reported that several mutations in the Gag and Env regions were involved in reduction in viral infection/production in vitro during endogenization, yet the negative impact of these and other mutations on viral replication has not been evaluated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of amino acid sequences between the two subgroups was 87.6%, and the variability was mainly found in variable region A (VRA), which is the major determinant of receptor usage (17), and the proline-rich region (PRR) of the envelope glycoprotein (Env). The CETTG motif, which is involved in fusion activity (18), was disrupted by mutations in both KoRV-A and KoRV-J. KoRV-J had a replacement of Gln with Arg in the PHQ motif, which is important for the fusion activity (19)(20)(21)(22).…”
mentioning
confidence: 99%